2016
DOI: 10.1002/mus.25116
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET detects nonuniform muscle activity in the lower body during human gait

Abstract: Nonuniform muscle activity is likely related to recruitment of motor units located within separate neuromuscular compartments. These findings indicate that neuromuscular compartments are recruited selectively to allow for efficient energy transfer, and these patterns may be task-dependent. Muscle Nerve 54: 959-966, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(82 reference statements)
1
1
0
Order By: Relevance
“…Muscular activity cannot, however, be assumed to be homogeneous throughout a given muscle [ 8 , 34 ]. As also found in previous studies, our results show that even though quadriceps were activated using a strictly controlled paradigm, there was a large variation in the measured activation among subjects, among individual muscle groups and even within a muscle [ 19 21 , 35 ]. However, the correlation between relΔ T 2 and relGU was found to be consistent in voxel by voxel comparisons and displayed the same inhomogeneous activation patterns.…”
Section: Discussionsupporting
confidence: 87%
“…Muscular activity cannot, however, be assumed to be homogeneous throughout a given muscle [ 8 , 34 ]. As also found in previous studies, our results show that even though quadriceps were activated using a strictly controlled paradigm, there was a large variation in the measured activation among subjects, among individual muscle groups and even within a muscle [ 19 21 , 35 ]. However, the correlation between relΔ T 2 and relGU was found to be consistent in voxel by voxel comparisons and displayed the same inhomogeneous activation patterns.…”
Section: Discussionsupporting
confidence: 87%
“…These studies found, for example, that the muscles in the lower leg were more active than those in the thigh and around the hip, and that FDG-PET could be used to assess muscle activity in deep muscles such as the gluteus minimus, iliacus, and tibialis posterior, which had previously been difficult to measure using surface electromyography [19, 20, 23]. However limited data on asymmetries between muscles in the left and right legs, and region-specific activation within muscles are available [22, 24, 25]. In part, this may have been due to the analyses of the FDG uptake data being limited to single slices of the PET scan, instead of taking the uptake in the entire muscle into account.…”
Section: Introductionmentioning
confidence: 99%